(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
The main objective of this study was to assess the overall physical state of the prehistoric rock paintings of the Spitzkoppe. This article presents an evaluation of the condition of the rock art at the Bushman Paradise site. Ideally, a condition survey should be carried out periodically and be used as a monitoring and evaluation tool. This article is a contribution to ideas and methods that can be used to develop integrated and informed conservation strategies for rock art sites in Namibia. It identifies and classifies the causes of deterioration or damage of the rock art at the Bushman Paradise. We argue that systematic documentation is crucial for site management purposes because it is from detailed documentation that a statement of significance of sites can be generated. We conclude from the analysis that anthropogenic causes of deterioration at the Bushman Paradise outweigh natural causes. We conclude by proposing site specific conservation interventions that can be replicated at other sites of similar nature in the Spitzkoppe and Namibia in general.